The Association Between Intake of Saturated, Monounsaturated, and Polyunsaturated Fatty Acids with Bifidobacterium Abundance Among Obese Adults Without Metabolic Syndrome - Rustanti, Ninik; Sinthika, Euodia; Lestari, Endang Sri (Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Bifidobacterium is a key gut microbe that contributes to host metabolism, immunity, and intestinal integrity through SCFA production. Dietary fats are known to modulate gut microbiota, but evidence on the effects of specific fat types—SFA, MUFA, PUFA—on Bifidobacterium in obese adults without metabolic syndrome remains limited.Objectives: To examine the association between intake of dietary fat types and the abundance of Bifidobacterium among obese adults without metabolic syndrome.Methods: A cross-sectional study was conducted in Semarang, Indonesia, involving 60 obese adults (BMI ≥ 25 kg/m²) without metabolic syndrome. Dietary intake was assessed using a validated SQ-FFQ, and Bifidobacterium abundance was quantified using qPCR from fecal samples. Correlation and multivariate linear regression - adjusted for age, sex, and energy intake - were used to assess associations between variables.Results: Saturated fat intake was moderately and negatively correlated with Bifidobacterium levels (r = –0.464; p < 0.001), while total fat intake also showed a statistically significant, but weaker, negative correlation (r = –0.346; p = 0.007). PUFA intake showed a weak but statistically significant positive correlation (r = 0.269; p = 0.037), whereas MUFA intake was not significantly associated. Multivariate analysis identified SFA as an independent negative predictor of Bifidobacterium abundance.Conclusion: High intake of saturated fat is associated with decreased Bifidobacterium levels even in obese adults without metabolic syndrome, whereas PUFA may exert modest protective effects. These findings suggest that the type of dietary fat, rather than its quantity, plays a key role in modulating gut microbiota composition.